O antropogênico e o geogênico na sedimentologia pré-histórica de Lagoa Santa: estudo geoarqueológico do Sítio Lapa do Niáctor - Leandro Vieira da Silva (2013)
The present study investigates, with the use of analytical techniques of Geoarchaeology, the degree of impact of human action on the formation of sedimentary process. The sedimentary matrices are traces that traditionally receive little investment by researchers, even though this is a key element for the interpretation of any archeological site. The possibilities that present in sheltered locations to better preserve the stratigraphy, led us to choose as a case study, the archaeological site Lapa do Niáctor located in Jaboticatubas, Minas Gerais. Its a rockshelter of limestone formation, which was attended by hunter-gatherer populations between 9.990 to 8.080 BP in the context of the archaeological area of Lagoa Santa. The object of study was focused on deciphering the material composition of sediments collected form archaeological excavations, which were mentioned there possibilities to explain the origin of these sediments. A review of the sedimentological process from five rockshelters occupied during the Old Holocene in Lagoa Santa Karst has been presented for purposes of contextalisation and comparison, and subsequently with the implementation of Mineralogy, Miromorphology and Fluvial Geomorphology in Lapa do Niáctors area, was possible to analyze the process of deposition and diagenesis occurred in matrix. Identification of the material offered, subsequently, the opportunity to conduct experimental fires that provided quantitative for discussion and subsequent interpretation of the functionality of that rockshelter in prehistoric times. The methodology employed shown to be feasible in the application of similar archaeological contexts, to examine issues related to sedimentological identification and use of rockshelter spaces.